1998
DOI: 10.1080/00039899809605722
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Power Frequency Magnetic Fields and Risk of Breast Cancer in the Upper Cape Cod Cancer Incidence Study

Abstract: Investigators used a population-based case-control study to evaluate the relationship between breast cancer risk and exposure to 60-Hz magnetic fields from various sources. There was no increase in breast cancer risk associated with (a) holding a job with high (odds ratio [OR] = 1.2; 95% confidence interval [CI] = 0.4, 3.4) or medium (OR = 0.9; 95% CI = 0.5, 1.7) exposure to magnetic fields; (b) living in a home heated electrically (OR = 1.0; 95% CI = 0.7, 1.4); or (c) sleeping with an electric blanket (OR = 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 31 publications
0
14
0
1
Order By: Relevance
“…Many of the studies used a broad definition of exposure based on either occupations (25,28,(31)(32)(33)(34) or qualitative job-exposure matrices (35)(36)(37)(38)(39). Some of these studies found evidence for an increased risk with potential exposure to EMFs (25,28,31,(35)(36)(37), whereas others did not (32,33; 38, 39).lnterestingly, the few studies incorporating quantitative exposure measurements found little to no evidence for an elevated breast cancer risk (40)(41)(42), largely consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the studies used a broad definition of exposure based on either occupations (25,28,(31)(32)(33)(34) or qualitative job-exposure matrices (35)(36)(37)(38)(39). Some of these studies found evidence for an increased risk with potential exposure to EMFs (25,28,31,(35)(36)(37), whereas others did not (32,33; 38, 39).lnterestingly, the few studies incorporating quantitative exposure measurements found little to no evidence for an elevated breast cancer risk (40)(41)(42), largely consistent with the results of our study.…”
Section: Discussionmentioning
confidence: 99%
“…Since then, and over the subsequent three decades, a considerable amount of epidemiological studies have analysed a potential association with breast cancer from ELF exposure in residential and occupational environments, including from electric blankets. However, most epidemiological studies have indicated little or no overall effect of ELF-MF exposure risks and similar findings are reported in the majority of studies of bed heating devices (Verkasalo et al, 1996;Li et al, 1997;Coogan & Aschengrau, 1998;Schoenfeld et al, 2003;Elliott et al, 2013).…”
Section: Breast Cancermentioning
confidence: 59%
“…Effects were visible at quite low exposure levels, as any exposure to magnetic fields >0.05 µT was associated with an increased risk of breast cancer. Similarly, the general outcomes from studies of occupational exposure did not indicate any effects either (Coogan & Aschengrau, 1998;Kliukiene et al, 2004;Forssén et al, 2005;McElroy, 2007). Furthermore, the metaanalysis studies (Erren, 2001;Chen et al, 2010) which, between them, summarised the literature available from 1966-2009, including studies analysing residential and occupational exposures, as well as those from electric blankets.…”
Section: Breast Cancermentioning
confidence: 99%
“…In our study, there were eight studies[3], [12], [15], [18], [20], [22], [25] that made an exposure assessment through investigating the usage of electric heating apparatus such as electric blanket, seven[11], [13], [21], [25], [26], [29], [30] through working history, five[16], [19], [24], [26], [29] through the exposure level of the living environment, two[21], [30] through measuring and calculating the ELF-EMF levels based on the living and working conditions. In the 23 studies, there were sixteen studies[3], [12][15], [17], [18], [20], [22][24], [27][29], [32] from America, three[19], [21], [31] from Sweden, two[26], [30] from Norway, one from Canada and one from Taiwan. In terms of case selecting, fourteen [3], [15][19], [21][24], [28], [29], [31], [33] studies selected their cases from cancer registry, other cases were selected from hospitals or other cohort studies.…”
Section: Resultsmentioning
confidence: 99%